The Judiciary and the 1979’s Constitution - Montoya Anguerry, Carlos (1981)
The objective of this paper is to analyze the functioning of the Judicial Branch in the context of the modifications introduced by the 1979 Peru's Political Constitution. To this end, the constitutional articles relating to the judiciary and its functioning will be examined, emphasizing the main changes with respect to the 1933 Constitution. It also examines how access to justice manifests itself in practice and the real complications. In conclusion, the 1979 Constitution grants more protection by recognizing additional aspects of the Judiciary, reinforcing its structure and functionality. However, more modifications should be considered to achieve its purpose.